Pengaruh Kompensasi, Pengawasan, dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT. Q - Tasya Amelia Wirdiana; Ian Nurpatria Suryawan (ARBITRASE: Journal of Economics and Accounting, 2022)
The purpose of this study was to determine the effect of compensation, supervision, and work discipline on employee performance at PT. Q. The population used in this study amounted to 67 employees. The sampling technique used in this study is saturated sampling where all the population is sampled as many as 67 permanent employees at PT. Q. The technique of collecting data is by distributing questionnaires using a Likert scale. Then the data were analyzed. Based on the results of the analysis of hypothesis testing in this study that compensation does not partially affect employee performance, while supervision and work discipline partially affect employee performance.